Expert opinion on the current conceptual, clinical and therapeutic aspects of disease related malnutrition and muscle loss: a multidisciplinary perspective - Doganay, Mutlu; Halil, Meltem Gulhan; Kaymak, Cetin; Selek, Ugur; Topcuoglu, Mehmet Akif; Yalcin, Suayib (Frontiers in Nutrition, 2025)
Disease-related malnutrition (DRM) and muscle related conditions (i.e., muscle loss, sarcopenia, and frailty) are overlapping but still underappreciated conditions, which independently and synergistically contribute to an increased risk of adverse health outcomes. Targeted nutritional interventions that can protect and even reverse the muscle loss besides the nutritional status are considered a key clinical priority to improve clinical outcomes and alleviate the joint burden of both malnutrition and muscle loss in malnourished or at-risk patients. Therefore, the proposed expert opinion aimed to address the current conceptual, clinical and therapeutic aspects of DRM and muscle loss from a multidisciplinary perspective in certain risk groups (geriatric patients, cancer patients, patients with neurodegenerative disorders and critically ill patients) and to address the utility of targeted specific nutritional interventions, specifically the high protein nutritional supplements containing β-hydroxy-β-methylbutyrate (HMB) and vitamin D, in terms of potential beneficial effects in preserving and reversing muscle loss beyond meeting nutritional requirements.